Numerical Analysis of a Micro Horizontal Axis Wind Turbine Tower Under Extreme Loads - Shuwa, M.; Muhammad , A. B.; Maina, M. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
One of the major challenges in the development of horizontal axis wind turbine is the selection of appropriate and cost effective tower that will elevate the rotor meters above the ground for wind energy harvest. In this work a tubular structural steel material having an external diameter of 0.1 m, internal diameter of 0.092 m and height of 10 m was selected based on cost, mechanical properties and market availability for the tower. Response of this tower material due to simultaneously applied extreme static, dynamic and aerodynamic loading conditions was analyzed in terms of frequency of vibration, deformation and stress using the numerical code COMSOL Multi-physics 5.2. Three dimensional model of the structural steel tower was developed and boundary conditions defined in the numerical code’s model wizard interface. The tower was considered as a cantilever and a static load of 2128.77 N was applied at 10 m height in the  plane.  Dynamic load of 413.96 N was applied on the tower in the x,y,z planes and an aerodynamic load of 4967.58 N  was applied as uniformly distributed loads in the x plane. Extra fine regular quadrilateral mesh was generated for the computation. Frequency response result of the transfer function at 110 GHz excitation shown in terms of electric field norm was uniformly distributed at the outer boundary layer of the tower with a minimum value of 3.7 x 10-79 V/m.  The result of the deformation analysis under the predefined extreme loading conditions shows a maximum deflection value of 197 mm at 10 m height and 0 mm at 0 m height of the tower. Additionally, the stress analysis result shows a predicted maximum value 3.28 x 106 N/m2   between 0 m and 1.98 m height of the tower in the wind direction. The deformation was within the elastic limit of the tower material, because the total exerted extreme loads without the self-weight of the tower (2,397.54 N) was less than the determined safe load of the tower (7,107.96 N). The study has established that the selected horizontal axis wind turbine (HAWT) tower material was reliable under the predefined simultaneously applied extreme loads, thus the structural steel tower can function in areas this or similar loading conditions.